Humanity as a Contested Concept: Relations between Disability and ‘Being Human’ - van Trigt, Paul (2016)
This editorial presents the theme and approach of the themed issue “Humanity as a Contested Concept: Relations between Disability and ‘Being Human’”. The way in which the concept of humanity is or must be related to disability is critically investigated from different disciplinary perspectives in the themed issue, which is, moreover, situated in the field of disability studies and related to discussions about posthumanism. The argument is made that humanity is a concept that needs to be constantly reflected upon from a disability studies perspective. Finally, the contributions of the themed issue are briefly outlined.